Accurate and fast identification of Campylobacter fetus in bulls by real-time PCR targeting a 16S rRNA gene sequence - Delpiazzo, Rafael; Barcellos, Maila; Barros, Sofia; Bentacor, Laura; Fraga, Martin; Gil, Jorge; Iraola, Gregorio; Morsella, Claudia Graciela; Paolicchi, Fernando; Perez, Ruben; Riet Correa, Franklin; Sanguinetti, Margarita; et al. (Elsevier, 2021)
Campylobacter fetus is an important animal pathogen that causes infectious infertility, embryonic mortality and abortions in cattle and sheep flocks. There are two recognized subspecies related with reproductive disorders in livestock: Campylobacter fetus subsp. fetus (Cff) and Campylobacter fetus subsp. venerealis (Cfv). Rapid and reliable detection of this pathogenic species in bulls is of upmost importance for disease control in dairy and beef herds as they are asymptomatic carriers. The aim of the present work was to assess the performance a real-time PCR (qPCR) method for the diagnosis of Campylobacter fetus in samples from bulls, comparing it with culture and isolation methods. 520 preputial samples were both cultured in Skirrow's medium and analyzed by qPCR. The estimated sensitivity of qPCR was 90.9% (95% CI, 69.4%–100%), and the specificity was 99.4% (95% CI, 98.6% - 100%). The proportion of C. fetus positive individuals was 2.1% by isolation and 2.5% by qPCR. Isolates were identified by biochemical tests as Cfv (n = 9) and Cff (n = 2). Our findings support the use of qPCR for fast and accurate detection of C. fetus directly from field samples of preputial smegma of bulls. The qPCR method showed to be suitable for massive screenings because it can be performed in pooled samples without losing accuracy and sensitivity.